Chemical, microstructural and mechanical properties of ceramic waste blended cementitious systems. (20th February 2019) - Lasseuguette, E.; Burns, S.; Simmons, D.; Francis, E.; Chai, H.K.; Koutsos, V.; Huang, Y.
Abstract: There is an emerging need for a sustainable and cost-effective source of Supplementary Cementitious Material (SCM) to reduce clinker consumption, as well as an effective utilisation of the ceramic waste stream. This study explores the potential of two types of ceramic waste tiles as SCMs by examining the mineralogical properties and mechanical performance of mortar and paste samples prepared with 5%, 15% and 30%wt of the ceramics ground into powder form as cement replacement. Investigations were carried out over a 90-day curing period by using standard methods including the XRD, DTA/TGA and SEM analyses, as well as the compression test. The pozzolanic reactivity of both ceramics has been validated with the presence of the secondary hydration reaction. This study concludes that a mortar mix containing 15% White ceramic could achieve a compressive strength comparable to that of a standard Ordinary Portland Cement (OPC) mortar at 56 days after curing, and even exceeds the strength of the latter beyond this age.